Identification of twenty one microsatellite loci for conservation genetic studies of the endemic butterflyfish Chaetodon tricinctus - van der Meer, M.; Gardner, M.; Hobbs, Jean-Paul; Pratchett, M.; Van Herwerden, L. (Springer, 2012)
Coral reef habitats are increasingly under threat from global warming and this has influenced the associated reef fish communities. Chaetodon tricinctus is a butterflyfish endemic to the offshore reefs of Elizabeth Reef, Middleton Reef, Lord Howe Island and Norfolk Island off Australia’s east coast. It is a highly specialised coral reef fish that is thought to rely on Acroporid coral species exclusively for food and shelter. We developed primers for twenty one microsatellite loci to reveal gene flow, population genetic structure and genetic diversity within and among these three reefs. Observed heterozygosities ranged from 0.185 to 0.964 and expected heterozygosities ranged from 0.230 to 0.889 in 30 individuals from Middleton Reef. When cross tested with Chaetodon trifascialis, a closely related species, there was poor amplification success and only a moderate level of polymorphism. Therefore, although these loci will be useful in C. tricinctus, it is unlikely that they can be used on other related butterflyfishes.